(untitled) (Physical Education, Health and Social Sciences, 2025)
This study looked at how teachers’ leadership skills, students’ confidence in their own abilities, and students’ engagement learning were related. The Krejcie and Morgan table was used to choose a sample of 144 students from a population of 230. We employed a five-point Likert scale to get the information. The reliability coefficients were 0.93 for leadership skills, 0.921 for self-efficacy, and 0.88 for student interest in learning. The results showed that all three factors were strongly related in a positive way. Also, students’ engagement in learning was partially mediating the effect of teachers’ leadership skills on students’ self-efficacy. These results show how important it is for instructors to be good leaders in order to help pupils feel confident and interested in studying. The results of the study have an impact on policy and practice in education. Based on the results, two main suggestions are made: Teachers should work on and improve their leadership abilities so that they can establish a learning atmosphere that is interesting and supportive, which will make students more interested in studying and boost their confidence. Schools should offer teachers professional development opportunities and training programs to help them become better leaders so they can better help children grow and learn.